Design of a continuous wave mud pulse generator for data transmission by fluid pressure fluctuation. (March 2018) - Yan, Zhidan; Geng, Yanfeng; Wei, Chunming; Wang, Tiannong; Gao, Tingzheng; Shao, Jing; Hu, Xiufeng; Yuan, Menglei
Abstract: High-speed downhole transmission technology is in high demand for measurement while drilling (MWD) and logging while drilling (LWD) systems which have had major roles in increasing the geo-steering and formation evaluation capacity of reach wells, difficult horizontal wells and branch wells as well as increasing drilling rates. This paper presents the conceptual design and performance of a novel continuous wave mud pulse generator with the goal of transmitting data using hydraulic pressure waves. The generator includes the rotary valve, drive shaft and bearings, rotary and static seals, motor and reducer, resolver, pressure balance structure and lower centralizer; all of these components are mounted within a rotary drill collar. In particular, the rotary valve is the key important part of the continuous wave mud pulse generator. Based on the concept of a sinusoidal signal output, an improved arc-fillet-line triangular valve orifice is designed according to the relationships between the fluid differential pressure of a thin-walled cutting edge and the fluid flow area calculated from the relative rotation angle of the rotor to the stator through the established polar coordinate equations. The highly similar sinusoidal pressure signals can be achieved by optimized valve structures, which were verified by computational fluid dynamics (CFD) simulations, where the valve flow pattern characteristics and the impact law between the gap of the stator/rotor and pressure waveform were also obtained. Moreover, the drive capability response curves of the motor driver unit with and without a load are precisely determined, and current ground hydraulic experiments indicate that the designed continuous wave mud pulse generator performs well as a whole. The generated real pressure waves exhibit clear spectrum structures with a distinctive characteristic signal. Highlights: The conceptual design of a novel continuous wave mud pulse generator is presented. The highly similar sinusoidal fluid pressure can be achieved by optimized triangular valve. CFD simulations show the valve flow pattern characteristics. Ground hydraulic tests indicate that the designed pulser performs well as a whole.